MATERNAL AND NEONATAL OUTCOMES WITH DIFFERENT ANAESTHETIC TECHNIQUES IN EMERGENCY LSCS: A SYSTEMATIC REVIEW AND META-ANALYSIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Emergency lower segment cesarean section (LSCS) is one of the most commonly performed obstetric surgical procedures worldwide. Selection of anaesthetic technique during emergency cesarean delivery plays a critical role in determining maternal and neonatal outcomes. General anaesthesia (GA), spinal anaesthesia (SA), epidural anaesthesia (EA), and combined spinal-epidural anaesthesia (CSE) are widely utilized techniques, each associated with specific advantages and risks. Objective: To compare maternal and neonatal outcomes associated with different anaesthetic techniques used during emergency LSCS through systematic review and meta-analysis. Methods: A systematic review and meta-analysis was conducted according to PRISMA 2020 guidelines. Electronic databases including PubMed, Scopus, Embase, Web of Science, and Cochrane Library were searched for studies published up to January 2026. Randomized controlled trials and observational comparative studies evaluating anaesthetic techniques in emergency LSCS were included. Primary maternal outcomes included hypotension, failed intubation, postoperative pain, postoperative nausea and vomiting, intensive care admission, and maternal mortality. Neonatal outcomes included Apgar scores, neonatal intensive care unit (NICU) admission, neonatal acidosis, and neonatal mortality. Random-effects meta-analysis was performed using pooled risk ratios (RR) and standardized mean differences (SMD). Results: Thirty-four studies involving 18,462 patients were included. Spinal anaesthesia was associated with significantly lower maternal postoperative pain scores and reduced postoperative nausea and vomiting compared with general anaesthesia. However, spinal anaesthesia demonstrated higher incidence of intraoperative hypotension (RR: 1.74; 95% CI: 1.42–2.11). General anaesthesia was associated with increased risk of failed airway management and respiratory complications. Neonatal outcomes favored neuraxial anaesthesia, with significantly higher 1-minute and 5-minute Apgar scores and lower NICU admission rates compared with general anaesthesia. No significant difference was observed in maternal mortality between techniques. Conclusion: Neuraxial anaesthetic techniques, particularly spinal anaesthesia, appear to provide superior maternal recovery and improved neonatal outcomes compared with general anaesthesia in emergency LSCS. However, careful hemodynamic monitoring is essential because of increased risk of maternal hypotension. Appropriate anaesthetic selection should be individualized based on maternal condition, fetal status, urgency of surgery, and institutional expertise.